Size as indicator of origin of salmon lice Lepeophtheirus salmonis (Copepoda: Caligidae) - Nordhagen, J.R.; Heuch, P.A.; Schra, T.A. (Contributions to Zoology, 2000)
Salmon lice Lepeophtheirus salmonis (Krøyer, 1837)from farmed Atlantic salmon have been implicated in the drastic sea trout and salmon stock declines found in Ireland and Norway. Can salmon lice from farmed and wild fish be distinguished? The hypothesis has been advanced that the treatment of salmon infested with salmon lice with organophosphate pesticides has resulted in the evolution of early maturing, smaller female lice, which are favoured because they have the chance to reproduce before treatment. Salmon lice on wild fish have been reported to be larger and have more eggs in their egg strings (sacks) than lice on farmed fish. The question is whether the size differences between the lice are genetically fixed or an expression of phenotypic plasticity. In this study, lice from wild and farmed fish were collected and measured, and it was found that the former were significantly larger. When larvae from these two sources were raised on salmon at the same temperature, they bad the same growth rate and morphology. Larvae from the wild lice were raised at 8.7°C and 12.2°C, and attained a significantly larger size at the lower temperature. These results suggest that the salmon louse size is plastic and consequently a poor indicator of salmon louse origin.